1982
DOI: 10.2135/cropsci1982.0011183x002200040023x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Okra‐Leaf, Frego‐Bract, and Smooth‐Leaf Mutants on Pink Bollworm Damage and Agronomic Properties of Cotton1

Abstract: Eight isolines of cotton, Gossypium hirsutum L., which carried all possible combinations of Okra leaf (L°2), frego bract (fg), and Smooth leaf (Sm2) vs. their normal‐leaf and normal‐bract equivalents in the La 71‐7 (a Stoneville) background, were grown in replicated experiments for 3 years in Arizona in insecticide‐free environments. Percentage of seed damage caused by pink bollworm (PBW), Pectinophora gossypiella (Saunders), and 11 agronomic properties were studied.Mean seed damage in the Okra‐leaf isolines w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
5

Year Published

1984
1984
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 0 publications
0
11
0
5
Order By: Relevance
“…The yield performance and boll rot disease resistance of okra leaf strains against normal leaf checks NIAB-78 and CRIS-9 was evaluated during 1997-98 season in randomized complete block design trial replicated four times. The trial received recommended agronomic practices without Increased egg/larval mortality Wilson and George (1982) and Wilson (1986) insecticide applications. The yield, quality characters and boll rot disease incidence data are presented in Table 2.…”
Section: Yield Comparison and Boll Rot Disease Incidence Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The yield performance and boll rot disease resistance of okra leaf strains against normal leaf checks NIAB-78 and CRIS-9 was evaluated during 1997-98 season in randomized complete block design trial replicated four times. The trial received recommended agronomic practices without Increased egg/larval mortality Wilson and George (1982) and Wilson (1986) insecticide applications. The yield, quality characters and boll rot disease incidence data are presented in Table 2.…”
Section: Yield Comparison and Boll Rot Disease Incidence Trialsmentioning
confidence: 99%
“…Okra leaf confers resistance to banded wing whitefly Jones et al (1975). Wilson and George (1982) indicated that okra leaf has considerable value against pink bollworms. Wilson (1986) showed that okra leaf breeding stocks in certain backgrounds have a modest level of resistance to pink bollworm and yield as much or more lint than do normal leaf cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Pubescent cottons were found to impede movement of larvae, causing exhaustion and disorientation, and additionally extending exposure of neonates to detrimental biotic (predators and parasites), and abiotic (high temperatures) conditions in the field (Smith et al 1975). Lower seed damage caused by pink bollworms was observed in okra leaf cotton isolines when compared with the normal leaf type (Wilson et al 1977(Wilson et al , 1979Wilson and George 1982;Wilson 1986). The earliness of the okra leaf varieties, the rapidity of flowering and boll development, the physical (thicker carpel wall) or chemical changes in the carpel wall, and the inability of larvae to penetrate the carpel wall were reported as the possible reasons for the reduced seed damage caused by pink bollworm (Wilson et al 1979.…”
Section: Introductionmentioning
confidence: 99%
“…Plantas de algodoeiro herbáceo com características morfológicas alternativas, tais como folha okra, bráctea frego e cor vermelha da planta, oferecem vantagens relacionadas à redução das lesões provocadas por inseto-praga (Jones, 1972;Wilson & George, 1982). Além disso, algodoeiros com folha okra ainda apresentam maior precocidade, maior produção de flores, melhor penetração de inseticidas, e reduzida incidência de maçãs apodrecidas, em comparação com algodoeiros de folha normal (Jones et al, 1980;Jones, 1982;Heitholt, 1993;Silva et al, 1996;Heitholt & Meredith Junior, 1998).…”
Section: Introductionunclassified